Judaism and Other Faiths - Cohn-Sherbok, D. author. aut Link
IX, 186 p.
Keywords: This pioneering study is the first full-length exploration of the relationship between Judaism and the world's religions. After tracing the history of Jewish views of other religious traditions, the author formulates a new Jewish theology of religious pluralism. This is a vital source for all those who seek to understand Judaism among the universe of faiths.